The Revolution Of 1903 In Serbia In The Eyes Of Russian Contemporaries - Tumanin, Victor (2018)
The beginning of the 20th century became for Serbia not just as "the next step on the time stairs", but radically changed all further history of the country. The revolution on May 29, 1903, having finished "autocracy" of the last Obrenoviches, opened the page of "constitutionality and national foreign policy of Karageorgevich dynasty" [Yugoslaviya v XX v. 2011]. In the Serbian historiography this short period of history of the Kingdom of Serbia is often treated as "the Golden Age of the Serbian parliamentarism". Some of authors even believe that at the beginning of the 20th century Serbians "created the modern system of parliamentary democracy", having brought closer the country to "the European samples" in the political plan.Inside politics of the Kingdom of Serbia after the revolution of 1903 undergo of certain transformations. Serious changes concerned the Serbian political parties. In particular, the Liberal party morph into the People's party; the Serbian Progressive Party was revived in 1906. The first elections after the revolution, also gave the vast majority to radicals, however split among the Serbian radicals which first symptoms were shown in 1901, raised at the Russian contemporaries doubts in ability of radicals to take the responsibility for effective management of the country "at that military terror which, apparently, finally triumphed now in Belgrade".